Communicative Language Teaching (CLT) in Improving Speaking Skills of Tertiary Level EFL Students of Bangladesh - Paulomi Rahman Nisha (Faculty of Education and Teacher Training of UIN Palopo, 2024)
In the English as a Foreign Language (EFL) context, students must be given a proper foundation of communication skills necessary in various dynamic real-world situations. This study investigates learner perception of the effectiveness of Communicative Language Teaching (CLT) in improving the speaking skills of tertiary-level EFL students in Bangladesh. A mixed-methods approach was used to collect and analyze data from 30 students, of different private universities of Bangladesh. The data was gathered by analyzing the results from the survey. The results of the study showed there was a statistically significant improvement in the speaking skills of EFL students after the CLT intervention. The students demonstrated an increase in fluency and complexity in their speaking performance. Furthermore, findings revealed that the students had positive perceptions of CLT and found it effective in enhancing their speaking skills. The findings of this study provide valuable insights into the benefits of using CLT as a teaching method in EFL environments. This suggests the importance of incorporating communicative and interactive activities in language classrooms to promote language learning and student engagement.